An experimental study of flame height and air entrainment of buoyancy-controlled jet flames with sidewalls. (1st November 2016) - Tao, C.F.; Shen, Y.; Zong, R.W.; Tang, F.
Highlights: Flame length and air entrainment addressing the effect of sidewalls for jet flames. The correlation of parameter C with hydraulic diameter has been developed. A global model is proposed to estimate the air entrainment of jet flames. Abstract: The flame height and air entrainment of jet flame from axisymmetrical source with sidewalls have been investigated in this paper. Two sizes of nozzle have been used, and seven kinds of spaces between the two sidewalls ( W  = 15, 20, 30, 40, 60, 80, and ∞ cm) with the same width have been considered. It is found that the flame height decreases with the increase of space between sidewalls, while the entrainment coefficient increases with it. The value of parameter C is generally inversely proportional to the hydraulic diameter of the sidewalls ( D ) linearly. The value of α 4 / 5 · L f is almost a constant for the same heat release rate Q ̇ under different spaces of sidewalls. A global model has been developed between α 4 / 5 · L f and Q ̇ with a linear relationship.